2019
DOI: 10.3892/ol.2019.10427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibiting ACAT‑1 expression on the growth and metastasis of Lewis lung carcinoma

Abstract: Accumulating evidence suggests that acetyl-CoA acetryltransferase 1 (ACAT-1) may mediate tumor development and metastasis. However, the specific function served by ACAT-1 in lung cancer is not well understood. Therefore, the present study initially verified that ACAT-1 was overexpressed in Lewis lung carcinoma (LLC) tissues compared with non-LLC mice and that this overexpression promoted the proliferation, invasion and metastasis of these LLC samples. Western blotting, immunofluorescence microscopy and flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Treatment of LLC cells with avasimibe caused a decrease in cell proliferation and migration. Moreover, avasimibe alone or in combination with cyclophosphamide was able to reduce both tumor growth and metastasis formation in xenograft mouse model ( 127 ).…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
“…Treatment of LLC cells with avasimibe caused a decrease in cell proliferation and migration. Moreover, avasimibe alone or in combination with cyclophosphamide was able to reduce both tumor growth and metastasis formation in xenograft mouse model ( 127 ).…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
“…Surprisingly, we found that the cholesterol esterification inhibitor avasimibe can inhibit the expression of SOAT1. Although this has been reported in other cancers, the conclusion is still under debate since the concentration of avasimibe used in the study was cytotoxic [ 15 , 34 ]. Further studies are needed to explore how avasimibe affects the expression of SOAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found no evidence that induction of CYP3A11 (the mouse homologue of CYP3A4) was tested for in any of the 24 pre-clinical SOAT inhibition studies. This included five studies which examined and suggested SOAT inhibition should be performed alongside chemotherapy treatment [53, 57, 65, 67, 85]. SOAT inhibitors that do not activate CYP3A4 should be considered instead.…”
Section: Discussionmentioning
confidence: 99%